The ABCA1/ApoE/HDL pathway mediates GW3965-induced neurorestoration after stroke - Cui, Xu (Stroke, 2016)
BACKGROUND AND PURPOSE: ATP-binding cassette transporter A1 (ABCA1) is a major reverse cholesterol-transporter and plays critical role in the formation of brain high-density-lipoprotein (HDL) cholesterol. Apolipoprotein-E (ApoE) is the most abundant apolipoprotein and transports cholesterol into cells in brain. ABCA1 and ApoE are up-regulated by liver-X-receptors. Activation of liver-X-receptors has neurorestorative benefit for stroke. We tested the hypothesis that ABCA1/ApoE/HDL pathway mediates GW3965, a synthetic dual liver-X-receptor agonist, induced neurorestoration after stroke. METHODS: Middle-aged male specific brain-ABCA1-deficient (ABCA1(−B/−B)) and floxed-control (ABCA1(fl/fl)) mice were subjected to distal middle-cerebral-artery occlusion (dMCAo) and gavaged with saline or GW3965 (10mg/kg), or intracerebral-infusion of artificial cerebrospinal-fluid or hHDL3 in ABCA1(−B/−B)–stroke mice, starting 24h after dMCAo and daily until sacrifice 14 days after dMCAo. RESULTS: No differences in the blood level of total-cholesterol and triglyceride and lesion-volume were found among the groups. Compared with ABCA1(fl/fl)-ischemic mice, ABCA1(−B/−B)-ischemic mice exhibited impairment functional-outcome and decreased ABCA1/ApoE expression, and decreased gray/white-matter densities in the ischemic-boundary-zone 14 days after dMCAo. GW3965-treatment of ABCA1(fl/fl)-ischemic mice led to increased brain ABCA1/ApoE expression, concomitantly to increased blood-HDL, gray/white-matter densities and oligodendrocyte-progenitor-cell numbers in the ischemic-boundary-zone as well as improved functional-outcome 14 days after dMCAo. GW3965-treatment had negligible beneficial effects in ABCA1(−B/−B)-ischemic mice. However, intracerebral-infusion of hHDL3 significantly attenuated ABCA1(−B/−B)–induced deficits. In vitro, GW3965-treatment (5μM) increased ABCA1/synaptophysin level and neurite/axonal-outgrowth in primary cortical neurons derived from ABCA1(fl/fl)-embryos, but not in neurons derived from ABCA1(−B/−B)-embryos. HDL-treatment (80μg/mL) attenuated the reduction of neurite/axonal-outgrowth in neurons derived from ABCA1(−B/−B)-embryos. CONCLUSIONS: ABCA1/ApoE/HDL pathway, at least partially, contributes to GW3965-induced neurorestoration after stroke.